Experimental Results on Charge Fluctuations in Heavy-Ion Collisions - D. K. Mishra; P. Garg; P. K. Netrakanti; L. M. Pant; A. K. Mohanty (Advances in High Energy Physics)
We present a subset of experimental results on charge fluctuation from the heavy-ion collisions to search for phase transition and location of critical point in the QCD phase diagram. Measurements from the heavy-ion experiments at the SPS and RHIC energies observe that total charge fluctuations increase from central to peripheral collisions. The net-charge fluctuations in terms of dynamical fluctuation measure ν(+-,dyn) are studied as a function of collision energy (sNN) and centrality of the collisions. The product of ν(+-,dyn) and 〈Nch〉 shows a monotonic decrease with collision energies, which indicates that at LHC energy the fluctuations have their origin in the QGP phase. The fluctuations in terms of higher moments of net-proton, net-electric charge, and net-kaon have been measured for various sNN. Deviations are observed in both Sσ and κσ2 for net-proton multiplicity distributions from the Skellam and hadron resonance gas model for sNN<39 GeV. Higher moment results of the net-electric charge and net-kaon do not observe any significant nonmonotonic behavior as a function of collision energy. We also discuss the extraction of the freeze-out parameters using particle ratios and experimentally measured higher moments of net-charge fluctuations. The extracted freeze-out parameters from experimentally measured moments and lattice calculations are found to be in agreement with the results obtained from the fit of particle ratios to the thermal model calculations.